Comparison of the Oocyte Quality Derived from Two-Dimensional Follicle Culture Methods and Developmental Competence of In Vitro Grown and Matured Oocytes. (4th April 2018) - Lee, Jaewang; Kim, Eun Jung; Kong, Hyun Sun; Youm, Hye Won; Kim, Seul Ki; Lee, Jung Ryeol; Suh, Chang Suk; Kim, Seok Hyun
Abstract : In vitro follicle growth (IVFG) is an emerging fertility preservation technique, which can obtain fertilizable oocytes from an in vitro culture system in female. This study aimed to compare efficiency of the most widely used two-dimensional follicle culture methods [with or without oil layer (O+ or O− group)]. Preantral follicles were isolated from mice and randomly assigned. Follicles were cultured for 10 days and cumulus-oocyte complexes harvested 16–18 hours after hCG treatment. Follicle and oocyte growth, hormones in spent medium, meiotic spindle localization, expression of reactive oxygen species (ROS), mitochondrial activity, and gene expression were evaluated. In follicle growth, survival, pseudoantral cavity formation, ovulation, and oocyte maturation were also significantly higher in O+ group than O− group. Hormone production was significantly higher in follicles cultured in O+ than O−. There were no significant differences in mRNA expression related to development. On the other hand, the level of ROS was increased while the mitochondrial activity of in vitro grown matured oocyte was less than in vivo matured oocytes. In conclusion, follicle culture with O+ group appears to be superior to the culture in O− group in terms of follicle growth, development, oocyte growth, maturation, and microorganelles in oocyte.